Representations of the Arab Spring in Contemporary Arabic Novels - Gelis, Rasha Abdel Fattah Mohamed (Journal of Humanities & Social Sciences, 2018)
Literature emanates from reality in all different political and social dimensions and the fact that the Arab Spring and its revolutions form a climax in the Arab world. This paper investigates the reflections of political realities that pertain to the Arab Spring and some of Arab revolutions that took place in the last few years (Egyptian, Libyan, and Syrian). As well, it traces its manifestations, ideological visions , the most important of characteristics of these events in terms of populism, the role of media, speed of revolution and the results. in the contemporary Arab novel, with much focus on these novels. IT Is Blood tackles The Egyptian scene, The Chivalry of Slain Dreams discuses Libyan scene, The Shell and They Hear its Whisper discus the Syrian scene. This analysis shows the weak literary analysis on the level of vision and formulation that its blood was the best work that presents the Egyptian revolution; whereas, The Chivalry of Slain Dreams was very weak on the level of construction. In addition to this, the Syrian experience was confined to the ideological vision. Moreover, the study shows the literary weakness that is resulted from the political realities of the political detainees.